Pengaruh Metode Masase Effleurage terhadap Nyeri Persalinan Kala I Fase Aktif Pada Ibu Inpartu di Klinik Sartika Manurung - Eka Ristin Tarigan; Adelina Fitri Tanjung (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Childbirth is a natural physiological process, but it is often accompanied by intense pain, especially during the first stage, the cervical dilation phase. This pain arises from uterine contractions, cervical dilation, and fetal pressure on the pelvic structures. For primiparous mothers, this experience of childbirth is a first-time experience that can cause anxiety, tension, and even trauma if not managed properly. The research design used in this study was a quasi-experimental study with a two-group pretest-posttest. The sample size in this study was 38 participants: 19 in the intervention group and 19 in the control group, using a simple random sampling technique. The data analysis used was the t-dependent and t-independent tests. The results of the study obtained the characteristics of the intervention group respondents, most of the respondents were aged 30-35 years as many as 8 people (40.1%), parity of 2 children as many as 8 people (38.5%), and education level was high school as many as 14 people (73.7%). While in the control group most of the respondents were aged 30-35 years as many as 7 people (32.8%), parity of 2 children) as many as 9 people (40.5%), and education level was high school as many as 18 people (94.7%). The intensity of pain in the intervention group before effleurage massage was an average of 6.26 and after an average of 5.74 while in the control group before massage was an average of 6.97 and after an average of 5.83. The results of the dependent t-test of pain intensity before and after effleurage massage in the intervention group obtained a P value of 0.000 and in the control group before and after massage obtained a P value of 0.006. The results of the independent t-test can be concluded that there is a significant difference after the effleurage massage method was carried out in the intervention group, namely a P value of 0.001. From the results of this study, it is known that there is an effect of the effleurage massage method on reducing the intensity of labor pain in the active phase of the first stage of labor in mothers inpartu. Therefore, it is recommended that midwives apply the effleurage massage method as an intervention to reduce pain in the care of mothers in normal labor. Keywords: ,